National Corrections Reporting Program, 1993 ([Verlag nicht ermittelbar], 1997)
This study was conducted to provide a consistent and comprehensive description of convicted persons' entrance into and departure from correctional custody and correctional supervision. To accomplish this goal, data were gathered from official state prison records on topics such as race, sex, and age of inmates, length of time in jail, length of time in prison, and type of offense committed. The data were collected from the state prison systems of 38 states, as well as the Federal Prison System, the California Youth Authority, and the District of Columbia.